Occult Untreated Alcohol Use Disorder in a Patient with Recurrent Pituitary Macroadenoma - Rowe, Mckenzie P.; Balasanova, Alëna A. (Case Reports in Psychiatry, 2022)
Alcohol use disorder (AUD) is a chronic relapsing and remitting psychiatric condition associated with adverse health outcomes. Although common, AUD is underdiagnosed, and treatment is often overlooked. At times of increased risk, such as the postoperative period, it is imperative to screen for and treat AUD to improve patient outcomes. Psychiatrists can play an important role in addressing AUD in this patient population through addiction psychiatry consultation services. We present the case of a patient with occult alcohol use disorder (AUD) leading to hospitalization in the setting of depressive mood symptoms and personality changes after a repeat pituitary macroadenoma resection and radiation five months earlier. AUD was noted months prior to hospitalization but was not addressed despite regular interactions with the healthcare system. Evaluation by addiction psychiatry specialists during hospitalization prompted recognition and treatment of AUD, resulting in cessation of alcohol use and resolution of mood symptoms and personality changes. The patient was discharged 3 days after admission and maintained abstinence from alcohol at two months postdischarge without recurrence of psychiatric symptoms.